Helper T‐cell signaling and inflammatory pathway lead to formation of calcium phosphate but not calcium oxalate stones on Randall's plaques. (28th March 2019) - Taguchi, Kazumi; Hamamoto, Shuzo; Okada, Atsushi; Sugino, Teruaki; Unno, Rei; Ando, Ryosuke; Gao, Bing; Tozawa, Keiichi; Kohri, Kenjiro; Yasui, Takahiro
Abstract : Objectives: To elucidate the difference in the lithogenesis of calcium oxalate and calcium phosphate stones. Methods: Renal papillary tissues were obtained from 23 idiopathic calcium oxalate and seven calcium phosphate stone patients who had undergone endoscopic lithotripsy. Samples were individually collected from two different regions in each patient: the papillary mucosa containing Randall's plaque and mucosa not containing Randall's plaque. A microarray analysis was carried out on those tissues to compare their gene expression patterns. Furthermore, a causal pathway analysis comparing their differences was carried out. Results: Cluster analysis showed that gene expression profiles of calcium phosphate stone patients markedly differed from those of calcium oxalate stone patients. Disease and function analysis showed that Randall's plaque‐containing tissues of calcium phosphate stone‐forming patients had significantly higher movement and migration of mononuclear leukocytes, and lower tendency toward infection and lymph node formation than Randall's plaque‐containing tissues of calcium oxalate stone formers. Additional pathway analysis showed increased immune cell signaling in calcium phosphate formers, such as the helper T cell 1 and 2 pathways, which was confirmed by their messenger ribonucleic acid expression. Conclusions: The present results show the upregulation of helper T‐cell signaling pathways in Randall's plaque‐containing papillae in calcium phosphate, but not in calcium oxalate stone formers. Thus, helper T‐cell immune responses and the related inflammatory processes seem to lead to the formation of calcium phosphate stones on Randall's plaques.